Jekleni detajl: Eifflov stolp (1884-89) - Slivnik, Lara (AR. Arhitektura, raziskave, 2004)
The article brings a short review of futuristic plans for unusually high forged and wrought iron towers, which were to be built as additional viewing buildings for the World fairs in the nineteenth century. The first to succeed in achieving his plan was Alexandre Gustave Eiffel for the World fair in Paris, as late as 1889. The three-hundred meter high tower couldn't be built without the use of a new material - steel, without new technological breakthroughs - use of elevators, water reservoirs and sewage, or without carefully thought out details - from the skeleton system of tower construction to details of jointing foundations to vertical beams and jointing details of horizontal beams in particular floors. The main focus of the article is on particular plans and descriptions of details. The Eiffel Tower was the subject of disputes and admiration; for more than forty years it was the World's highest building and still remains one of the pinnacles of nineteenth century engineering architecture.
Keywords: inženirska arhitektura; svetovne razstave; Eifflov stolp; Pariz